1965
DOI: 10.1007/bf02636912
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of nuclear magnetic resonance and dilatometry for estimating solids content of fats and shortenings

Abstract: The percent solids values of fats and shortenings using nuclear magnetic resonance (NMR) and solid fat index (SFI) have been compared. The samples used were: blends of hard fat and safflower oil, safflower oil hydrogenated to varying degrees, and different types of shortenings. This investigation demonstrated the empirical nature of the SFI technique and shows the nature of the deviations from the solids content determined by the NMR method. The magnitude of the deviation of SFI from the NMR solids content inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…In order to properly account for these it would be necessary to have detailed data on the specific lipid composition considered. Because this is not only cumbersome but also impractical average values are used resulting in data obtained from standard dilatometry of fat compositions of limited accuracy . As improvement of this approach it was suggested to determine the density of fat compositions via vibrating tube density meters .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to properly account for these it would be necessary to have detailed data on the specific lipid composition considered. Because this is not only cumbersome but also impractical average values are used resulting in data obtained from standard dilatometry of fat compositions of limited accuracy . As improvement of this approach it was suggested to determine the density of fat compositions via vibrating tube density meters .…”
Section: Introductionmentioning
confidence: 99%
“…Because this is not only cumbersome but also impractical average values are used resulting in data obtained from standard dilatometry of fat compositions of limited accuracy. [7][8][9][10][11][12] As improvement of this approach it was suggested to determine the density of fat compositions via vibrating tube density meters. [7] Even though beneficial compared to dilatometry this method has not gained much attention.…”
Section: Introductionmentioning
confidence: 99%
“…The wideline NMR technique (5)(6)(7)(8)(9)(10)(11)(12) provided the first attempt at a direct measurement of solids in fats since it depended on the dipole-dipole interactions of rotating glyceride molecules~ This approach compares the area under a liquid signal at a given temperature with that of a reference oil. Pohle et al (7) indicated that the precision of the wideline NMR method decreases with increasing solids level. Swindells and Ferguson (11) found that a dilatometric type of tempering was necessary to eliminate anomalous sample behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Since Chapman and co-workers (1) introduced the wide line NMR technique for the determination of the amount of solid phase in fats, this method has been studied by various authors (2)(3)(4)(5)(6)(7)(8). However, since they all worked with the same type of instrument (Schlumberger NMR analyzer or Varian PA-7), they also come to more or less the same conclusions.…”
Section: Introductionmentioning
confidence: 99%